350 Examining the effect of a butyrate-fortified milk replacer on gastrointestinal microbiota and fermentation in dairy calves at weaning. (7th December 2018) - O Hara, E; Kelly, A; McCabe, M; Kenny, D; Guan, L; Waters, S
Abstract: With rising opposition to the prophylactic use of conventional antimicrobials in livestock production, there is increasing interest in the development of diet-derived alternatives. Butyrate is a short-chain fatty acid (SCFA) produced throughout the gastrointestinal lumen by gut microbiota, and is the primary energy source of rumen epithelial cells and colonocytes. Work from our group and others has demonstrated beneficial effects of exogenous butyrate on animal and intestinal growth, but little is known about its impact on the gut microbiota. To address this, 44 Holstein-Friesian bull calves were placed shortly after birth on a standard 49-d calf rearing protocol, and randomly assigned to SB (milk replacer plus sodium butyrate, n=22) or CON (milk replacer only, n=22) treatment groups. Water and concentrates were offered ad libitum. At weaning on D56, 8 animals from each group were randomly selected for slaughter. Following euthanasia, the intestinal tract was quickly exteriorised and digesta samples from the rumen, cecum, and colon were collected and snap frozen. SCFA profiles in the rumen and colon were assessed using gas chromatography. Amplicon sequencing of the partial 16S rRNA gene was used to assess the rumen and hindgut microbiota. SB had no impact on taxonomic composition in the rumen, but bacterial diversity and the concentration of butyrate were reduced (P < 0.05). In the hindgut, toal SCFA, propionate and acetate concentrations were increased by SB (P < 0.05) and the abundances of several cecal taxa were also changed. These included reductions in butyrate producers Butyrivibrio and Shuttleworthia in the SB calves, while the propionate producer Phascolarctobacterium was increased (P < 0.05). Increased SCFA may contribute to the improved growth previously observed in SB supplemented calves. In conclusion, the positive benefits of SB on growth and performance occur in tandem with changes in the abundance of important SCFA producing bacteria and fermentation patterns in the hindgut.